Colonic perforation as an unusual manifestation of Behcet's disease - Tomić-Lučić Aleksandra (Vojnosanitetski Pregled, 2011)
Introduction. Behcet's disease is multisystemic vasculitis which affects vein and artery blood vessels. Intestinal perforation rarely occurs as clinic manifestation in as litle as 1% of patients. The transverse colon is the most infrequent site of perforation. We presented a patient diagnosed with Behcet's disease who underwent both surgical and conversative treatment due to perforation of the colon. Case report. A 34-year-old patient was admitted to the hospital with fever, aphthous ulcerations on oral mucosa and genitals and bilateral uveitis. On the basis of clinical symptoms and the International Criteria developed in 1990 Behcet's disease was diagnosed. During the next few days the patient developed erythema nodosum, diarrheic syndrome and acute abdominal symptoms due to perforation of the transverse colon. An emergent laparotomy was undertaken involving resection of a perforated segment of the colon, and bipolar colostomy on the left side of abdomen. Following the surgery the patient was treated except for antibiotics with three successive pulse doses of methylprednisolone (500 mg/daily) and cyclophosphamide (15 mg/kg). The treatment was continued by gradual decrease in the close of the corticosteroid (perorally) and by cyclophosphamide first with monthly doses (5 monthly pulse doses of 15 mg/kg cyclophosphoamide), and then with 3-month doses (totally 6 doses) up to totally 12 g. Conclusion. The therapy with pulse doses of methylprednisolone combined with pulse doses of cyclophosphamide was very effective in the reported case with the complex clinical manifestations leading to resolution of gastrointenstinal, ocular and orogenital lesions.